Reviews. (1st November 2018) - Zhang, Shuai; Xu, Xiaoyan; Bicer, Elcin; Herbert, Carrie; Demaine, Krystal; Morrison, Amy
Digital Bodies: Creativity and Technology in the Arts and Humanities, Susan Broadhurst And Sara Price (eds) (2017) London: Palgrave Macmillan, 270 pp., ISBN: 978-1-34995-240-3, h/bk, 99.99Acting, Spectating and the Unconscious: The Psychoanalytic Perspective on Unconscious Processes of Identification in the Theatre, Maria Turri (2016) New York: Routledge, 132 pp., ISBN: 978-1-31551-733-9, eBook, 28.98Nourish: Cambodia's 1st Creative Arts Therapy and Wellbeing Conference, Phnom Penh, 16–18 January 2018The Indigenous Roots of Expressive Arts Therapy: Report on the 12th Biannual International Expressive Arts Therapy (IEATA ) Conference, Winnipeg, 4–8 October 2017